Lier les cooccurrences des Epithetes (1571) de Maurice de La Porte et celles des textes de la Pléiade - Nathalie Gasiglia; Anne-Pascale Pouey-Mounou (Corela)
This article analyses the constraints and methodological choices involved in processing a pre-modern lexicographical corpus that is stylistically usable. It is based on the example of a current editorial project that involves processing and publishing, in digital format, a sixteenth century lexicographical work, Les Epithetes by Maurice de La Porte (1571), whose main source is the poetry of the Pléiade. The textual database currently being established should make it possible to identify the attestations upon which La Porte based his selections. The database is intended to be both an analytical tool and the preparatory phase for a digital edition of the work. It features original search functions based on the annotation of the attestations that will enrich La Porte’s text. The article underlines the specificity of this dictionary of collocations in modern and sixteenth century lexicographical output, and discusses the constraints inherent in this particular corpus. These relate to its rhetorical purpose, as well as to the state of the French language at the time and the interpretation of the lexicographer. The article illustrates these constraints via two concrete examples of how corpora can be used, so as to present the informative potential of the data and the strategies that can be implemented to exploit it.